Method to Analyze Three-Dimensional Cell Distribution and Infiltration in Degradable Scaffolds - Thevenot, Paul (Mary Ann Liebert, Inc., 2008)
Effective cell seeding throughout the tissue scaffold often determines the success of tissue-engineering products, although most current methods focus on determining the total number, not the distribution, of the cells associated with tissue-engineering constructs. The purpose of this investigation was to establish a quick, convenient, and efficient method to quantify cell survival, distribution, and infiltration into degradable scaffolds using a combination of fluorescence cell staining and cryosectioning techniques. After cell seeding and culture for different periods of time, seeded scaffolds were stained with a live cell dye and then cryosectioned. Cryosectioned scaffolds were then recompiled into a three-dimensional (3D) image to visualize cell behavior after seeding. To test the effectiveness of this imaging method, four common seeding methods, including static surface seeding, cell injection, orbital shaker seeding, and centrifuge seeding, were investigated for their seeding efficacy. Using this new method, we were able to visualize the benefits and drawbacks of each seeding method with regard to the cell behavior in 3D within the scaffolds. This method is likely to provide useful information to assist the development of novel materials or cell-seeding methods for producing full-thickness tissue grafts.